IL233, an IL-2-IL-33 hybrid cytokine induces prolonged remission of mouse lupus nephritis by targeting Treg cells as a single therapeutic agent. (August 2019) - Stremska, Marta E.; Dai, Chao; Venkatadri, Rajkumar; Wang, Hongyang; Sabapathy, Vikram; Kumar, Gaurav; Jose, Sheethal; Mohammad, Saleh; Sung, Sun-sang J.; Fu, Shu Man; Sharma, Rahul
Abstract: Lupus glomerulonephritis (GN) is an autoimmune disease characterized by immune complex-deposition, complement activation and glomerular inflammation. In lupus-prone NZM2328 mice, the occurrence of lupus GN was accompanied by a decrease in Treg cells and an increase in proinflammatory cytokine-producing T cells. Because IL-33 in addition to IL-2 has been shown to be important for Treg cell proliferation and ST2 (IL-33 receptor) positive Treg cells are more potent in suppressor activity, a hybrid cytokine with active domains of IL-2 and IL-33 was generated to target the ST2 + Treg cells as a therapeutic agent to treat lupus GN. Three mouse models were used: spontaneous and Ad-IFNα- accelerated lupus GN in NZM2328 and the lymphoproliferative autoimmune GN in MRL/ lpr mice. Daily injections of IL233 for 5 days prevented Ad-IFNα-induced lupus GN and induced remission of spontaneous lupus GN. The remission was permanent in that no relapses were detected. The remission was accompanied by persistent elevation of Treg cells in the renal lymph nodes. IL233 is more potent than IL-2 and IL-33 either singly or in combination in the treatment of lupus GN. The results of this study support the thesis that IL233 should be considered as a novel agent for treating lupus GN. Highlights: Lupus prone NZM2328 mice have a deficit in IL-2, IL-10 and Foxp3 + ST2 + Tregs. IL-2 and IL-33 combination in the form of IL-2 and IL-33 fusion cytokine (IL233) induced a sustained increase in Tregs and suppressed inflammation without affecting autoantibodies. IL233, as a single agent not only prevented the onset, but also induced persistent remission in ongoing lupus glomerulonephritis (GN) in IFNα-accelerated and spontaneous models in NZM2328 mice and in MRL/ lpr mice.